2018
DOI: 10.1155/2018/8741698
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Derived Anti-HIV Polysaccharide Peptide (PSP) Triggers a Toll-Like Receptor 4-Dependent Antiviral Immune Response

Abstract: Aim Intense interest remains in the identification of compounds to reduce human immunodeficiency virus type 1 (HIV-1) replication. Coriolus versicolor's polysaccharide peptide (PSP) has been demonstrated to possess immunomodulatory properties with the ability to activate an innate immune response through Toll-like receptor 4 (TLR4) showing insignificant toxicity. This study sought to determine the potential use of PSP as an anti-HIV agent and whether its antiviral immune response was TLR4 dependent. Materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…Moreover, mushrooms have been reported to show immunomodulating activity. They could be used in combination with drugs to initiate and support immune responses [ 31 , 35 ]. Synergism between a mushroom extract and antiviral drug has also been reported [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, mushrooms have been reported to show immunomodulating activity. They could be used in combination with drugs to initiate and support immune responses [ 31 , 35 ]. Synergism between a mushroom extract and antiviral drug has also been reported [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The water extract also showed good anti-FIV-RT activity. It has been reported that some proteins and polysaccharides extracted from mushrooms showed antiviral potential [ 12 , 24 , 25 , 27 , 29 , 31 , 32 , 35 , 37 , 38 ] ( Table-2 ). Thus, the experimental design to obtain the anti-FIV compounds (e.g., type of inhibitor, solvent used, and purification method) should be taken into account in further studies and clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…The polysaccharides from mushrooms exhibited potential anti-HIV activity by downregulating replication of the virus and upregulating certain antiviral chemokines (Stromal Cell Derived Factor-1 alpha, SDF-1α, and Macrophage Inflammatory Protein, MIP-1α/β). These chemokines block the coreceptors of HIV-1 in THP1 cells from leukemia patients and blood mononuclear cells [26]. Table 1.…”
Section: The Role Of Food Ingredients and Active Compounds In Supportmentioning
confidence: 99%
“…The findings presented here are in agreement with those published by other authors, who stated that the mechanism underlying the anti-viral activity of mushroom extracts may be related to the inhibition of viral adsorption and penetration [6, 9, 39]. Mushroom protein-bound glycan isolated from Polystictus Versicolor , PSK or Krestin, which are currently used as adjunctive therapies for various types of cancers in Japan, showed promising potential as anti-HIV agents by downregulating viral replication and promoting the upregulation of specific antiviral chemokines (RANTES, MIP-1 α / β , and SDF-1 α ) known to block HIV-1 coreceptors in THP1 cells and human PBMCs [40].…”
Section: Discussionmentioning
confidence: 99%